Energy dispersive X‐ray fluorescence analysis to estimate the maximum temperature reached in burned soils from an Amazonian region. Issue 1 (13th November 2022) - Rocha, Débora Rodrigues; Thomaz, Edivaldo Lopes; Urbano, Alexandre; Vendrame, Pedro Rodolfo Siqueira; Melquiades, Fábio Luiz
Abstract: Determining the maximum temperature reached in soil during burning is important when evaluating fire intensity. Forest conversion is an ongoing process in the Amazon ecosystem. It is of utmost importance to predict fire effects on soil properties and avoid damaging environmental systems. Spectroscopic methods combined with multivariate statistics may provide chemical and mineralogical information from soil. This study aims at predicting the maximum temperature reached in Oxisols from an Amazonian region in Brazil. Slash‐and‐burn and pasture samples collected after fire events and unburned forest soil samples submitted to heating (250–800 °C) were investigated. Energy‐dispersive X‐ray fluorescence (EDXRF) was used to acquire chemical data. The experimental procedure is rapid and requires minimal sample preparation and no hazardous chemical reagents. The EDXRF data, combined with partial least squares regression, were applied in controlled‐heated samples from five different sites of forest, pasture, and slash‐and‐burn areas. Estimated temperatures for burned samples ranged from 317 to 609 °C. Considering the instrumental advantages and the achieved results, the use of EDXRF combined with multivariate analysis is a feasible alternative technology to evaluate fire effects in soil. Core Ideas: Maximum temperature reached in soils was estimated by PLS regression models. Soil properties were evaluated rapidly and environmental‐friendly by EDXRF. Feasible alternative technology was investigated to evaluate fire effects in soil properties. Innovative method was developed to estimate the maximum temperature reached in the soil after burning.